Studies of magnetization dynamics in magnetic recording media and patterned yttrium iron garnet films - Richardson, Daniel, author; Wu, Mingzhong, advisor; de la Venta Granda, Jose, committee member; Kabos, Pavel, committee member; Krueger, David, committee member; Marconi, Mario, committee member (Colorado State University. Libraries, 2018)
Exchange coupling and damping are studied in magnetic media materials for applications in current perpendicular magnetic recording (PMR) technology as well as future heat assisted magnetic recording (HAMR) media technology. Damping and exchange coupling are directly related to magnetization switching time in writing operation and the signal-to-noise ratio in reading, both critical to the performance of hard disk drives. Intergranular exchange is studied in current PMR media to see how exchange is altered in the presence of SiO2 based segregant. By varying the segregant by as much as 30%, there is strong tunability of the exchange field between the grains. The damping in future FePt-based HAMR media is studied near the curie temperature (725 K) of FePt where the writing stage in the recording media takes place. The trends of ferromagnetic resonance (FMR) linewidth varying with the sample temperature, the volume fraction of carbon in the media, and the angle of the external field indicate that the overall damping includes strong contributions from intrinsic magnon-electron scattering as well as extrinsic two-magnon scattering between the grains. Interlayer exchange coupling and damping were studied in magnetic layered systems consisting of a soft ferromagnetic transition metal or alloy layer and a hard FePt layer at room and elevated temperatures. It was found that exchange coupling and damping are strongly dependent on temperature, the soft layer thickness, and the choice of material of the soft layer. Spin waves are studied in the linear and non-linear regimes using magnonic crystals consisting of yttrium iron garnet (YIG) thin film strips with periodic etched lines or periodic metallic lines deposited on top of the YIG strip, as well as YIG strips with randomly spaced metallic lines deposited on top. The various media provide ways of controlling the dispersion by altering the interference of the spin waves, allowing for a wide range of interesting phenomenon to be observed. Spin-wave fractals are observed for the first time in a YIG strip with periodic etched lines. The etched lines serve as position dependent potentials to increase dispersion in the YIG strip large enough for fractal formation in the nonlinear regime. This is also the first time fractals of any type that have been observed without the formation of time-domain solitons. Spin-wave localization is observed in the linear regime for the first time in YIG strips with randomly spaced metallic lines where the metallic lines serve as potential barriers for causing spin wave interference. Magnonic crystals consisting of YIG strips with periodically spaced metallic lines are used to compare a standing wave state with the localized state. The localized state is much stronger and much more confined to a smaller physical space than the standing wave state.
Keywords: magnetic recording media; spin waves; magnetization; ferromagnetic resonance